Pergeseran Stratifikasi Sosial Masyarakat dalam Tradisi Metuun Teruna Desa Adat Subagan - Anistarini, Ni Kadek; Arjawa, I Gusti Putu Bagus Suka; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
ABSTRACT This study aims to analyze the shift in social stratification of society in the metuun teruna tradition of Subagan Traditional Village. The theory used is the status theory of Ralph Linton, which divides social status into three types, namely assigned status, ascribed status and achieved status. This study uses a qualitative method with data collection techniques through in-depth interviews, observation and documentation of the Subagan Traditional Village community. The results of the study indicate that the shift in social stratification of society in the metuun teruna tradition occurred at the highest strata which initially came from village officials or assigned status shifted to individuals with established economic capabilities. This shift is motivated by two factors, namely internal factors and internal factors. These internal factors are the desire for a higher social status, comparing self-achievement with others, increasing the economic capabilities of the community, and changes in lifestyle and consumption. External factors of the shift in stratification in the Subagan Traditional Village community are globalization and modernization, urbanization, and more equitable education. This study concludes that the shift in social stratification of society is clearly visible in the implementation of the metuun teruna tradition where social groups with established economic capabilities or those referred to as achieved status show their achievements through various consumption symbols, thus creating admiration and appreciation from other communities so that other social groups such as village officials or assigned status do not receive the same appreciation as before. Keywords: social stratification, social status, local tradition, metuun teruna